Adenoid glioblastoma - Cui-yun SUN; Shi-zhu YU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Objective To report the diagnosis and treatment of one case of adenoid glioblastoma and investigate the clinicopathological features, diagnosis and differential diagnosis. Methods and Results A 63-year-old male patient suffered from left-skewed corner of the mouth for more than 10 d. Brain enhanced MRI revealed a cystic mass in left frontotemporal lobe and metastatic tumor was considered. 18F-fluoro-2-deoxy-D-glucose (18F-FDG) PET did not detected any sign of malignant neoplasm in the whole body. Under the guide of neuronavigation and ultrasound, the tumor was totally removed under microscope. Histologically, the tumor was located in brain parenchyma and presented a growing pattern of multicentric sheets or nests. Mucus scattered in some regions. Tumor cells were arranged in strip, cribriform, adenoid or papillary patterns. Tumor cells contained few cytoplasm with round or oval uniform hyperchromatic nuclei and occasionally obvious nucleoli. Proliferation of glomeruloid vascular endothelial cells could be seen. Immunohistochemical staining showed the cytoplasm of tumor cells was diffusively positive for glial fibrillary acidic protein (GFAP), vimentin (Vim) and phosphatase and tensin homologue (PTEN); nuclei was positive for oligodendrocytes transcription factor-2 (Olig-2) and P53; cytoplasm and nuclei were positive for S-100 protein (S-100); membrane was positive for epidermal growth factor receptor (EGFR). The tumor cells showed a negative reaction for cytokeratin (CK), epithelial membrane antigen (EMA), carcinoembryonic antigen (CEA), thyroid transcription factor-1 (TTF-1), CD31, CD34, CAM5.2 and isocitrate dehydrogenase 1 (IDH1). Ki-67 labeling index was 76.80%. The final pathological diagnosis was adenoid glioblastoma. The patient died of respiratroy failure and circulation function failure 12 d after operation. Conclusions Adenoid glioblastoma was a rare glioblastoma subtype. A clear diagnosis depends on histological findings and immunohistochemical features. It should be differentiated from metastatic adenocarcinoma.